Implementation of Wireless User Authentication using WLC-Forti Framework - Ignatius Agus Supriyono; Irwan Sembiring; Adi Setiawan; Iwan Setyawan; Theophilus Wellem; Henderi; Ilham Hizbuloh (Aptisi Transactions On Technopreneurship (ATT), 2023)
Internet access at this time is a daily necessity that cannot be denied. It is certain that most institutions and business entities require internet access in carrying out their activities, including educational institutions. With the development of mobile computer technology in which more users use mobile devices to access the internet, wireless-based network infrastructure is a demand that cannot be postponed any longer. By using a wireless connection to connect to the network, authentication becomes something that must be considered, the use of access to the network by unwanted parties can harm other parties. Changing passwords regularly is important to avoid misuse of access to the network by other parties. This paper presents a problem where when an educational institution implements the Bring Your Own Device (BYOD) program, students and teachers cannot change passwords using the personal device used, this is because the personal device is not registered with the domain controller at the institution. The solution proposed in this article is to move the NPS RADIUS server function on the local site to LDAP in the cloud using a combination of WLC which handles Wi-Fi clients and Fortinet which handles authentication to the cloud. The implementation results show that the WLC-Forti framework functions well.